Intercalation Of Rhodamine B Dye Into Zinc-Aluminum Layered Double Hydroxides: Structural, Textural, And Morphological Insights - Nursyafiqah Jori Roslan; Nur Nadia Dzulkifli; Tengku Shafazila Tengku Saharuddin; Hamizah Mohd Zaki; Syawal Mohd Yusof; Sheikh Ahmad Izaddin Sheikh Mohd Ghazali (Walailak University, 2026)
Indexed by SCOPUS / MYCITE